Office-to-Residential Conversion in Jakarta CBD: Stakeholder Perceptions, Structural Adaptability, and Implementation Barriers - Nabasa, Ester Dorothy (RUAS, 2026)
This study examines the feasibility of converting office buildings into residential units in Jakarta's Central Business District (CBD), responding to rising office vacancy rates and growing demand for inner-city housing. Using an exploratory qualitative approach grounded in grounded theory, the study analyzes seven case studies through document review and semi-structured interviews with architects, developers, and urban planners. The research covers technical, regulatory, and socio-spatial variables. Findings reveal that conversion feasibility is constrained by structural limitations such as rigid floor configurations, outdated utilities, and high retrofit costs, alongside regulatory barriers including inflexible zoning and complex permitting processes. Socio-spatial factors — community resistance and user expectations — also shape project outcomes. On the other hand, buildings near mass transit with adaptable structural systems show considerably higher conversion potential. The study argues that technical readiness alone is insufficient. Sustainable adaptive reuse requires supportive policy frameworks, integrated governance, and well-targeted incentives to move beyond case-by-case conversions toward a scalable urban strategy.